The Fletcher Theory Papers for Piano Class or Individual Instruction: Book Two (2+2+2+2+2+2+2+2+2+2+2+2) - FLETCHER, Leila (The Boston Music Co., 1945)
Buku ini tentang kertas teori fletcher untuk kelas piano atau instruksi individu.